Bruce Chatwin and His Journey through Patagonia: The Nomad Who Became a Writer - López Hernández , Isabel (The Grove - Working Papers on English Studies, 2020)
The British writer Bruce Chatwin (1940-1989) travelled to Patagonia in search of an answer to the question which conditioned his literary career: why do men travel instead of staying at home? The result of that journey was the analysis of the nomad spirit that he suffered and made him change places constantly. This article intends to study the awakening of his passion for nomadism and to examine how his experience in Patagonia transformed him into a literary traveller hurt by a nostalgic desire to be a nomad. He became a hero who set off for an intellectual answer to the heart of his yearning for travelling.